Anti-Dandruff Activities of Ethanol Extract and Water, N-Hexan, Ethyl Acetate Fractions of Key Lime (Citrus Aurantifolia) Leaves Against Malassezia Furfur - Resmi Mustarichie (Journal of Global Pharma Technology, 2020)
The objective of this research was to determine the Anti-dandruff characteristic of ethanol extract and its fractions of key-lime leaves (Citrus aurantifolia L) against the fungus Malassezia furfur. C. Aurifolia leaves were collected from villagers' vegetable crops in Kendari, Southeast Sulawesi, Eastern Indonesia. It was macerated with ethanol 96%, rotary evaporated till viscous extract was obtained. The extract was analyzed its phytochemical substances and tested its Minimum Inhibitory Concentration (MIC). The extract was fractionated using ethyl acetate and n-hexane. Both ethanol extract and its fractions were tested their anti-dandruff activity using the fungus Malassezia furfur. DMSO was used as negative control and ketoconazole 1% as a positive control. All data were statistically analyzed. Phytochemical screening found that key-lime leaves contained flavonoids, polyphenols, saponins, steroids & triterpenoids, and tannin. The results showed that key-lime leaf extract was able to inhibit the activity of the Malassezia furfur fungus, the inhibition zones of the extract were 1% (6.0 mm), 4% (7.55mm), 8% (8.44 mm), 16% (9.9 mm), and 29% (16.7) mm) which was slightly greater than 1% ketoconazole as a positive control. The higher the concentration of lime leaf extract, the greater the inhibitory power against the Malassezia furfur fungus. Statistical data shows that the fraction of key-lime leaf had the best antifungal effect shown by the ethyl acetate fraction. The study concluded that either ethanol extract or its fractions of c.aurantifolia leaves has anti-dandruff activity against M. furfur. The ethyl acetate fraction was found to have a better activity compared to n-hexane and water fractions. This finding could be useful to elucidate the compound which is responsible for this action. Keywords: Citrus aurantifolia, Anti-dandruff, MIC, Malassezia furfur, Ethanol extract.